Voluntary Work‐related Technology Use during Non‐work Time: A Narrative Synthesis of Empirical Research and Research Agenda. (3rd November 2017) - Schlachter, Svenja; McDowall, Almuth; Cropley, Mark; Inceoglu, Ilke
Abstract: The Internet and mobilization of information and communication technologies (ICTs) have made non‐manual work increasingly portable and remotely accessible. As a result, a considerable number of employees use their ICTs to engage in work‐related tasks during designated non‐work time, even without contractual obligation. However, existing research on such voluntary work‐related ICT use remains fragmented and spread across disciplines. The authors conducted a narrative review of 56 studies to identify themes in existing research, synthesize the evidence base and identify gaps in understanding. They identify five themes: (1) Social‐normative organizational context, (2) Job‐related characteristics and work processes, (3) Person characteristics, (4) Designated non‐work time and well‐being, and (5) Empowerment/Enslavement Paradox. A conceptual model of voluntary ICT use is developed by integrating the identified themes with existing organizational research, outlining the relationships between the identified themes and voluntary ICT use. The discussion emphasizes the need for more conceptual clarity on voluntary ICT use and related constructs, and for the integration of different disciplines and methodological approaches to advance knowledge in the field. The authors further identify person‐centred research as a critical future avenue to explore different ICT user types. Additionally, more research into the mechanisms and moderating influences regarding voluntary ICT use and its outcomes is considered advisable to advance knowledge on the Empowerment/Enslavement Paradox and its potential resolution. The paper concludes with preliminary implications to inform practice, addressing the need for employers to provide control over voluntary ICT use and employees enacting this control.